1984
DOI: 10.2136/sssaj1984.03615995004800040047x
|View full text |Cite
|
Sign up to set email alerts
|

Konyaite in Salt Efflorescence from a Tertiary Marine Deposit near Geelong, Victoria, Australia

Abstract: Konyaite [Na2Mg(SO4)2·5H2O] was identified for the first time in Australia in salt efflorescences from a Tertiary marine deposit below exposed basalt flows at a quarry near Geelong, Victoria. Other soluble salts in the efflorescence were epsomite (MgSO4·7H2O), gypsum (CaSO4·2H2O), and halite (NaCl). Heating at 110°C converted the konyaite to a mixture of bloedite [Na2Mg(SO4)2·4H2O], loeweite [Na4Mg2(SO4)4·5H2O], and thenardite (Na2SO4). Recrystallization at 23°C of the efflorescence dissolved in varying amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Anhydrite is generally not very common in the southwestern United States because its stability requires high temperatures and low relative humidities. Konyaite is also generally thought to be relatively unstable (Van Doesburg et al, 1982;Shayan and Lancucki, 1984;Kohut and Dudas, 1993) and has not been found in this region. Thus, the most common sets of hydrous/anhydrous minerals in the southwestern United States are thenardite/mirabilite, glauberite/eugsterite, and gypsum/bassanite (± anhydrite).…”
mentioning
confidence: 95%
“…Anhydrite is generally not very common in the southwestern United States because its stability requires high temperatures and low relative humidities. Konyaite is also generally thought to be relatively unstable (Van Doesburg et al, 1982;Shayan and Lancucki, 1984;Kohut and Dudas, 1993) and has not been found in this region. Thus, the most common sets of hydrous/anhydrous minerals in the southwestern United States are thenardite/mirabilite, glauberite/eugsterite, and gypsum/bassanite (± anhydrite).…”
mentioning
confidence: 95%
“…Little is * E-mail: leduc@geoladm.geol.queensu.ca known about the field of stability of konyaite; Keller et al (1986a) reported having found konyaite between 6.3 and 37.9 °C, but no relative humidity constraints were provided. They suggested however, as Shayan and Lancucki (1984) did before them, that konyaite typically forms in nature and dehydrates to form blödite, and that although direct formation of blödite is possible, the required conditions for its formation do not occur as frequently as those required for konyaite. Its status as a metastable phase (van Doesburg et al 1982;Friedel 1976) has also been questioned by Timpson et al (1986), although its soluble nature and sensitivity to relative humidity changes make it subject to remobilization into the local watershed.…”
Section: Introductionmentioning
confidence: 94%
“…the Na 2 O-MgO-SO 4 -H 2 O system (Shayan and Lancucki 1984). The mineral appears to form in disequilibrium with its parent saline solution, and to alter to blödite within a matter of days at room temperature, if the crystals stay in contact with the solution (Friedel 1976).…”
Section: Bond Lengths and Anglesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that goethite, rather than hematite, coexists with nontronite further indicates a low-temperature alteration. Shayan and Lancucki (1984) found that the ground water moving through the green basalt at Geelong had the composition (mmole/liter) of Na (88.8), Mg (8.5), Ca (0.85), Sr (0.01), CO32-(1.2), HCO3-(11.2), SO42-(3.94), and C1-(86.0) and a pH of 8.34. This composition may have been reached by river water moving through the surrounding Tertiary marine deposits before it intersected the basalt flow.…”
Section: Relationship Between Natural and Synthesized Materialsmentioning
confidence: 99%